The Di2/pet Variant in the PETALOSA Gene Underlies a Major Heat Requirement-Related QTL for Blooming Date in Peach [Prunus persica (L.) Batsch]. (5th January 2021) - Cirilli, Marco; Gattolin, Stefano; Chiozzotto, Remo; Baccichet, Irina; Pascal, Thierry; Quilot-Turion, Bndicte; Rossini, Laura; Bassi, Daniele
Abstract: Environmental adaptation of deciduous fruit trees largely depends on their ability to synchronize growth and development with seasonal climate change. Winter dormancy of flower buds is a key process to prevent frost damage and ensure reproductive success. Temperature is a crucial environmental stimulus largely influencing the timing of flowering, only occurring after fulfillment of certain temperature requirements. Nevertheless, genetic variation affecting chilling or heat-dependent dormancy release still remains largely unknown. In this study, a major QTL able to delay blooming date in peach by increasing heat requirement was finely mapped in three segregating progenies, revealing a strict association with a genetic variant ( petDEL ) in a PETALOSA gene, previously shown to also affect flower morphology. Analysis of segregating genome-edited tobacco plants provided further evidence of the potential ability of PET variations to delay flowering time. Potential applications of the petDEL variant for improving phenological traits in peach are discussed.